2021
DOI: 10.1108/bij-01-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Robotic process automation for industry: adoption status, benefits, challenges and research agenda

Abstract: PurposeThis study intends to find the industries that have leveraged Robotic Process Automation (RPA) technology and elucidate the extent of the adoption of RPA in various industry domains with benefits. The identification of tasks eligible for RPA itself is a challenge. Therefore, the study further brings out the challenges faced in various industry verticals and postulates the future direction of research and applications in RPA.Design/methodology/approachThe study focuses on articles from popular databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…The similar findings were presented by Bejaković and Mrnjavac (2020). The skills and competencies of the team, as well as the culture, ethics and behaviour of people in the organisation, determine the outcome of RPA implementation (Kedziora & Penttinen, 2021;Pramod, 2022). Anagnoste (2018) pointed out that among the non-technical competencies, leadership, communication, team working and problem-solving skills, new technology awareness play an important role in process design and its further automation.…”
Section: Digital Design and Process Automation Skills In Factory Of T...supporting
confidence: 60%
“…The similar findings were presented by Bejaković and Mrnjavac (2020). The skills and competencies of the team, as well as the culture, ethics and behaviour of people in the organisation, determine the outcome of RPA implementation (Kedziora & Penttinen, 2021;Pramod, 2022). Anagnoste (2018) pointed out that among the non-technical competencies, leadership, communication, team working and problem-solving skills, new technology awareness play an important role in process design and its further automation.…”
Section: Digital Design and Process Automation Skills In Factory Of T...supporting
confidence: 60%
“…Existing literature reviews indicated a variety of perspectives on RPA in general and in specific circumstances. For example, Pramod (2021) conducted SLR in the RPA field with an emphasis on the business and management field. Although various studies provide an overview of RPA, the great majority have concentrated on its application and implementation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this study, we set out to derive a corresponding framework. Based on a structured review of the literature and an analysis of 19 expert interviews, we identify 32 Critical Success Factors which we subsume in several contextual clusters Pramod (2022) 3…”
Section: Robotic Process Automationmentioning
confidence: 99%